Demonstrating the feature of energy saving of transforms in secondary schools - Király, Sándor (Teaching Mathematics and Computer Science, 2012)
When we are teaching the digital image formats and we are explaining the JPEG format we may get into difficulties how to explain the point and the usefulness of the discrete cosine transform (DCT) to our students. Why do we need this transform before compressing? Students probably do not know that the feature of energy saving of this transform makes the chance of good compression. In this article we show how we can demonstrate that feature of these transforms which make the chance of good compression while saving the most energy of images.